1999
DOI: 10.1029/1998jd200061
|View full text |Cite
|
Sign up to set email alerts
|

Comparative responses of EPIC and CERES crop models to high and low spatial resolution climate change scenarios

Abstract: Abstract. We compared the responses of the CERES and EPIC crop models, for wheat and corn, to two different climate change scenarios of different spatial scales applied to the central Great Plains. The scenarios were formed from a high-resolution regional climate model (RegCM) and a coarse resolution general circulation model, which provided the initial and boundary conditions for the regional model. Important differences in yield were predicted by the two models for the two different scenarios. For corn, CERE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 25 publications
4
66
0
2
Order By: Relevance
“…300 km in the atmospheric module of HadCM3). However, this resolution is generally insufficient to serve climate impact applications (Hostetler 1994;Mearns et al 2001), many of which require information at much finer scales to predict impacts in, say, river flow (Bell et al 2006) or crop growth (Mearns et al 1999). A method is therefore needed of obtaining realizations of fine-scale climate physically consistent with the simulations of large-scale climate obtained from GCMs.…”
Section: (I ) Downscaling Transient Changes For Impact Assessments (Bmentioning
confidence: 99%
“…300 km in the atmospheric module of HadCM3). However, this resolution is generally insufficient to serve climate impact applications (Hostetler 1994;Mearns et al 2001), many of which require information at much finer scales to predict impacts in, say, river flow (Bell et al 2006) or crop growth (Mearns et al 1999). A method is therefore needed of obtaining realizations of fine-scale climate physically consistent with the simulations of large-scale climate obtained from GCMs.…”
Section: (I ) Downscaling Transient Changes For Impact Assessments (Bmentioning
confidence: 99%
“…These include multiple crop models with multiple climate models (Mearns et al 1999;Asseng et al 2013;Li et al 2015), multiple crop and climate models with multiple parameters (Tao et al 2009) and multiple parameter values with multiple values for inputs (Aggarwal 1995).…”
Section: Super Ensemblesmentioning
confidence: 99%
“…It is therefore not surprising that both fields have major programs related to model intercomparison and the construction of multi-model ensembles (MMEs). However, the climate modeling community began working with MMEs with the Atmospheric Model Intercomparison project in 1989 (Gates et al 1999), whereas global collaboration to create crop multi-model ensembles began in 2011 with the Agricultural Modeling Intercomparison and Improvement project ), though more limited intercomparison studies predated that project (e.g., Jamieson et al 1998;Mearns et al 1999). Progress in the use of ensembles of both climate and crop models in studies of climate change is discussed in (Challinor et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to improve weather and climate variability, especially over complex terrain (see ref. 16 For agricultural impacts, initial studies suggested that dynamical downscaling may improve projections, because the use of RCMs altered modeled crop yields by up to 20% (22)(23)(24)(25)(26)(27)(28)(29). These studies were not definitive, however; they covered limited areas and times, which can increase GCM-RCM differences, and most used the delta method to remove climate model bias, which can reduce differences.…”
mentioning
confidence: 99%